2023
DOI: 10.3389/fbioe.2023.1065597
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel synthesis of lithium doped mesoporous bioactive glass nanoparticles and tricalcium silicate for restorative dentistry: Comparative investigation of physico-chemical structure, antibacterial susceptibility and biocompatibility

Abstract: Introduction: The sol-gel method for production of mesoporous bioactive glass nanoparticles (MBGNs) has been adapted to synthesize tricalcium silicate (TCS) particles which, when formulated with other additives, form the gold standard for dentine-pulp complex regeneration. Comparison of TCS and MBGNs obtained by sol-gel method is critical considering the results of the first ever clinical trials of sol-gel BAG as pulpotomy materials in children. Moreover, although lithium (Li) based glass ceramics have been lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 97 publications
3
4
0
Order By: Relevance
“…The 29 Si MAS NMR results showed that the incorporation of Li and Co significantly decreased the degree of polymerization and network connectivity of the silicate network of the MBGNs. However, the FTIR spectra showed no significant differences among the four types of MBGNs, which was in agreement with previous studies ( Kargozar et al, 2016 ; El-Fiqi and Kim, 2021 ; Simila and Boccaccini, 2023 ). It is possible that Ca 2+ , Li + , and part of the Co 2+ exist in the silicate network as modifiers, which are ionically linked to nonbridging oxygen atoms, and it is not easy for FTIR to detect the ionic bonds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 29 Si MAS NMR results showed that the incorporation of Li and Co significantly decreased the degree of polymerization and network connectivity of the silicate network of the MBGNs. However, the FTIR spectra showed no significant differences among the four types of MBGNs, which was in agreement with previous studies ( Kargozar et al, 2016 ; El-Fiqi and Kim, 2021 ; Simila and Boccaccini, 2023 ). It is possible that Ca 2+ , Li + , and part of the Co 2+ exist in the silicate network as modifiers, which are ionically linked to nonbridging oxygen atoms, and it is not easy for FTIR to detect the ionic bonds.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, Li-MBGNs were smaller than uMBGNs, consistent with the results of a previous study ( Simila and Boccaccini, 2023 ); however, explanations for this were not provided. The incorporation of Co 2+ results in nanoparticle agglomeration.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, MBGNs are excellent substrates for the loading of various active components, including antibiotics, growth factors (Cheng et al, 2018;Kim et al, 2016) and metal ions such as copper and zinc (Li et al, 2021;Schuhladen et al, 2020), for various treatments. Previous studies have confirmed that MBGNs are suitable for dentine regeneration (Choi et al, 2020;Jung et al, 2019;Simila & Boccaccini, 2023;Zhu et al, 2021). Therefore, we postulated that MBGNs loaded with antiinflammatory Ce ions could serve as a pulp-capping agent for the dentine regeneration.…”
Section: Introductionmentioning
confidence: 67%
“…Other ions were evaluated and used in biomedical applications, such as lithium [82], synthesized and characterized the morphology and chemical structure of tricalcium silicate (TCS) and MBGNs doped with 0%, 5%, 10%, and 20% Li using the sol-gel method. Subsequently, concentrations of 15 mg per 10 mL were incubated in artificial saliva, Hank's balanced salt solution, and simulated body fluid at 37 • C for 28 days.…”
Section: Mms Based On Silicon and Titanium Derivates As Antimicrobial...mentioning
confidence: 99%
“…Bone formation [77] MBGNs/copper ions S. aureus Antibacterial [78] Phosphate-based mesoporous glasses/ Cu ions S. aureus, E. coli Bioabsorbable materials [79] Zn-MBG S. aureus, E. coli Implants-associated infections [80] Zn/SBA-1/SBA-15 E. coli, B. subtilis Bone regeneration [81] Tricalcium silicate/MBGNs/Li S. aureus, E. coli Biomedical applications [82] MBGNs/Ce-Co S. aureus Wound healing [83] Na and colleagues presented an approach against antimicrobial infections by combining antibiotics with photothermal therapy using multifunctional nanomaterials [84]. In this study, the inherent photothermal efficiency of two-dimensional rhenium disulfide (ReS 2 ) nanosheets was heightened by coating them on mesoporous silica nanoparticles (MSNs) to create a highly efficient light-responsive nanomaterial with controlled-release drug delivery capabilities, known as MSN-ReS 2 .…”
Section: Aureusmentioning
confidence: 99%